Thermal properties of polymer materials in laser sintering process - Pham, Duc Trung; Shwe, S.; Wan Yusoff, Wan Ahmad Yusmawiza; Purwanto, Hadi; -, Farizahani (2011)
The objective of this research is to study the thermophysical properties of polymer materials used in Selective Laser Sintering (SLS). There are seven virgin SLS materials which are PA, GF, Alumide, PrimeCast, PrimePart DC, Duraflex and CastForm. Differential Scanning Calorimetry (DSC) was used in finding the melting point and the degradation energy of samples. The melting point of all samples are in the range of 81-191˚C. PrimeCast requires 0.76mJ/mg of latent heat for it to degrade while other samples require higher latent heat. Optical microscope was used to observe the particles of the materials while Fritsch Particle Sizer was used to analyze the average particle size of the materials. Images taken from the optical microscope confirm the present of glass bead in PA3200GF. The shape of particles in other materials is irregular. The results from Fraunhofer calculation show that only Alumide and CastForm fall within the recommended average particle size of 75-150µm. Fourier Transform Infrared Spectroscopy (FTIR) was used to analyze the chemical composition of the materials by using infrared radiation and absorbed frequency. The spectra show that similar functional groups were found in the materials apart from PrimePart DC and Duraflex.